WEB APPLICATION FOR DISTANCE EDUCTION - ZEGHBA et NABI, MOKHTAR et ABD-ELKADER (FACULTY: MATHIMATICS AND COMPUTER SCIENCE DEPARTEMENT: COMPUTER SCIENCE - OPTION : RTIC, 2021)
In this note, we dealt with a group of ideas and concepts and discussed their origin and history, such as distance education, online education, distance education platforms and many more ...., until we came up with our idea, which is the distance education platform for non-university levels, and in this context we proposed The way to embody the idea from diagrams and tools to pictures of what we have accomplished and presented.
Keywords: WEB APPLICATION : DISTANCE EDUCTION